STUDI LITERATUR: FENOMENA LITERASI NETIZEN INDONESIA MELALUI FEEDBACK DI SOSIAL MEDIA - Chadijah, Siti (CV. Lafadz Jaya, 2024)
The background problems in this research are numerous. Recent research shows that technology, especially the internet, creates such a big negative impact. Therefore, researchers agree that literacy media is needed to prevent this impact. There are also various media literacy studies carried out to find the right literacy model. This research aims to find out Literature Study: Literacy Phenomenon of Indonesian Netizens through Feedback on social media. The method used in this study is a library approach. The research results show that Most researchers conduct media and digital literacy research based on the high level of consumption of conventional and new media which indirectly has a negative effect on audiences. It is feared that this effect will damage the values and behavior of the public. Therefore, media and digital literacy is very much needed. This is because media and digital literacy teaches audiences to think critically when consuming media. Media literacy research trends in Indonesia are relatively like research trends at the international level. Most researchers examine media literacy as part of preventing the negative impacts of media rather than as a skill for self-empowerment.